The Protection of Ecological Rights of Peatland Communities in Indonesia’s National Legal Policy: A Legal and Human Rights Perspective Analysis - Hanafi, Hanafi; Tista, Adwin; Rahman, Muhammad Ghazali; Azizah, Noor (Scholar Center, 2025)
The peatland ecosystem in Indonesia, covering an area of 33.4 million hectares, plays a strategic role as a carbon sink, a water regulator, a habitat for biodiversity, and a foundation of community livelihood in economic, social, and cultural dimensions. However, its sustainability is increasingly threatened by land conversion, natural resource exploitation, and infrastructure development that neglects ecological principles. Weak governance, development policies prioritizing investment, and limited community participation have resulted in environmental degradation, agrarian conflicts, and the erosion of local communities’ ecological rights. Constitutionally, the right to a good and healthy environment is guaranteed under Article 28H paragraph (1) and Article 33 paragraph (3) of the 1945 Constitution, as well as Law No. 32 of 2009 on Environmental Protection and Management. This recognition is further reinforced by international instruments such as the 1972 Stockholm Declaration, the 1992 Rio Declaration, the 2015 Paris Agreement, and the Sustainable Development Goals (SDGs), which affirm environmental rights as part of third-generation human rights. Nevertheless, the implementation of ecological rights protection continues to face challenges, including weak law enforcement, limited access to justice, and the dominance of economic paradigms. This study examines the protection of ecological rights of peatland communities within Indonesia’s national legal policy through a human rights perspective, while also analyzing its harmonization with international law. The study is expected to contribute to strengthening regulation, advancing conservation strategies, and formulating policies grounded in ecological justice and human rights.